2022
DOI: 10.1038/s43018-022-00470-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the bicarbonate transporter SLC4A4 overcomes immunosuppression and immunotherapy resistance in pancreatic cancer

Abstract: Solid tumors are generally characterized by an acidic tumor microenvironment (TME) that favors cancer progression, therapy resistance and immune evasion. By single-cell RNA-sequencing analysis in individuals with pancreatic ductal adenocarcinoma (PDAC), we reveal solute carrier family 4 member 4 (SLC4A4) as the most abundant bicarbonate transporter, predominantly expressed by epithelial ductal cells. Functionally, SLC4A4 inhibition in PDAC cancer cells mitigates the acidosis of the TME due to bicarbonate accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…Mazzone and colleagues have demonstrated that PDAC cells express SLC4A4 a transporter that actively imports bicarbonate. 91 The accumulation of bicarbonate in PDAC cells increases intracellular pH, which in turn buffers against the accumulation of H + ions that are generated by glycolysis. This buffering allows glycolysis to proceed at a faster rate generating increased levels of H + /lactate, which PDAC cells readily export into the interstitial space.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%
“…Mazzone and colleagues have demonstrated that PDAC cells express SLC4A4 a transporter that actively imports bicarbonate. 91 The accumulation of bicarbonate in PDAC cells increases intracellular pH, which in turn buffers against the accumulation of H + ions that are generated by glycolysis. This buffering allows glycolysis to proceed at a faster rate generating increased levels of H + /lactate, which PDAC cells readily export into the interstitial space.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%
“…NBC transporters are able to load or extrude protons from the cell via sodium-bicarbonate transport. NBCe1, a type of NCB transporter, is present in pancreatic cancer cells and functions as an acid extruder that supports tumoral growth and metastasis ( Cappellesso et al, 2022 ). iii) Monocarboxylate transporters (MCT).…”
Section: Hv1 Channel In Cancer Biology: Ph Control As One Of the Gove...mentioning
confidence: 99%
“…At the same time, these therapeutic efforts aim to reverse the secondary tumoral environmental-extracellular acidification (TME) characteristic of the CPR of malignant cells and tissues. CPR is also a fundamental factor in the escape of malignant tumors from the organism's immune defense mechanisms [66,67].…”
Section: Therapeutic Implications: Closing Gapsmentioning
confidence: 99%